Modulation Processes in Power Electronic Converters - Ioannou, Stelios; Argyrou, Maria C.; Darwish, Mohamed K.; Marouchos, Christos (My University, 2020)
This work presents an in-depth analysis and identifies the inherent modulation processes in power converters relating input and output parameters to a switching function. The timing of the switching instances and duration of the on/off periods applied to the semiconductor power switches constitutes a Switching Function. The steady state response of two popular power converters is first investigated: The AC to DC Controlled Rectifier and the PWM sinusoidally modulated 3-Level H-Bridge inverter. Both share the same power circuit configuration, namely the H-Bridge. For both configurations an appropriate switching Function acts on the input voltage to produce the output voltage in an amplitude modulation process. The same Function acts on the output current to set the input current in a similar way. The expressions relating output and input (and vice versa) with the switching function are exactly the same and easily derived from the voltage current waveforms; it is the switching function that differs. Next the mathematical models of the two converters in the time domain are derived based on the fundamental switching function expressions. The novelty here is that they are not exactly "averaging models". The switching action of the semiconductor switches is taken into account to a good degree thus giving the harmonics on output and input current. The derived models are verified using the PSIM simulation software.
Keywords: Modulation Processes; Converters; Inverters; H-Bridge; Switching Function; Modulation Function